Unbalanced reciprocal translocations at amniocentesis - Chih-Ping Chen; Pei-Chen Wu; Chen-Ju Lin; Schu-Rern Chern; Fuu-Jen Tsai; Chen-Chi Lee; Dai-Dyi Town; Wen-Lin Chen; Li-Feng Chen; Meng-Shan Lee; Chen-Wen Pan; Wayseen Wang (Elsevier, 2011)
Objective: To present perinatal findings, modes of ascertainments, and modes of segregation in unbalanced reciprocal translocations detected at amniocentesis. Materials and Methods: Between January 1987 and July 2010, 40 cases with unbalanced reciprocal translocations were diagnosed by amniocentesis at Mackay Memorial Hospital, Taipei, Taiwan. The 40 cases originated from 29 families; 21 families with one case, 7 families with two cases, and 1 family with five cases. Results: Of 40 cases, 33 (82.5%) presented fetal ultrasound abnormalities and 7 (17.5%) presented no ultrasound abnormalities. Of 40 cases, 36 (90%) had a segregation mode of adjacent-1 2:2 segregation, 3 (7.5%) had a segregation mode of 3:1 segregation with tertiary trisomy, and 1 (2.5%) had a segregation mode of 3:1 segregation with tertiary monosomy. Of 29 families, 7 (24.1%) had de novo translocations and 22 (75.9%) had inherited translocations. In seven de novo cases, the main modes of ascertainments included abnormal ultrasound findings (n = 5) and advanced maternal age (n = 2). In 22 inherited families, the main modes of first ascertainment included abnormal ultrasound findings (n = 8), a previous aneuploid child (n = 8), advanced maternal age (n = 4), parental carrier status (n = 1), and abnormal maternal serum screening results (n = 1). Among 22 inherited families, 9 (40.9%) had a known parental carrier status, but 13 (59.1%) were unaware of parental carrier status at amniocentesis. Conclusion: Unbalanced reciprocal translocations detected at amniocentesis are frequently associated with abnormal ultrasound findings. Prenatal diagnosis of an unbalanced translocation may incidentally detect a balanced translocation in the family. Prenatal diagnosis of fetal structural abnormalities should alert structural chromosome rearrangements and prompt cytogenetic analysis of the fetus and parents if necessary.